Improving liquefaction process of microgrid scale Liquid Air Energy Storage (LAES) through waste heat recovery (WHR) and absorption chiller - Borri, Emiliano (2018)
Liquid air energy storage systems (LAES) store liquid air produced by a liquefaction cycle and convert it into electric/cooling power when needed. A small-scale Liquid air energy storage system represents a sustainable solution in microgrid and distributed generation, where small energy storage capacities are required. The main drawback of these systems though, is the low round trip efficiency due to a high specific consumption of the liquefaction cycle. In this work, a single-effect absorption chiller using a Water-Lithium Bromide solution is integrated with a small air liquefier with a liquid air production capacity of 0.834 t/h. In the proposed solution, the waste heat of the compression phase of the liquefaction cycle is recovered and used to drive the absorption cycle, where the resulting cooling power is used to decrease the specific consumption and improving the exergy efficiency of the system. The operative parameters of the absorption chiller reflect the specifications of the most common commercial models available in the market and the size has been selected to maximize the heat power recovered. The results of simulation of the absorption chiller integration show a reduction of the specific consumption of around 10% (537 kWh/t to 478 kWh/t) and an increase of exergy efficiency of around 11.5%.